Effect of a VITAFERT microbial additive on some bioproductive and health indicators in growing pigs - L. Lazo-Pérez (Cuban Journal of Agricultural Science, 2017)
In order to evaluate the effect of VITAFERT on some bioproductive and health indicators of growing pigs under production conditions, two groups of animals of 240 pigs each were used. Group A represented the control, and B was supplied with 10 mL of VITAFERT/kg of live weight as a supplement in the feed. The food intake, the increase, the average daily gain, food conversion and viability were determined, as well as the occurrence of diarrheal episodes by recording the epizootic indexes of morbidity, mortality and lethality, associated with diarrheal processes. The relative risk was also estimated through the conformation of 2 x 2 contingency tables, applying an observational analytical study of cohort type and an economic valuation of the application of the product was carried out. It is concluded that the pigs supplemented with VITAFERT improve the bioproductive indicators of live weight increase, average daily gain, feed conversion and viability. They also show lower rates of morbidity, mortality and lethality before diarrhea. The risk of death in pigs that did not intake VITAFERT was higher than in those supplemented with this product and death losses were higher in pigs that did not intake VITAFERT.